The Effect of Vertical and Horizontal Core Trainings on Core Strength, Agility and Speed - Durmuş Ali Tınkır; Ahmet Uzun (Selcuk University, 2022)
The aim of this study is to investigate the effect of core training in vertical and horizontal planes on core strength, speed and agility. Handball players aged 15-18 participated in the study (n=36); are divided into 3 groups as vertical core training group, horizontal core training group and control group. The average age of the handball players participating in the study is 16.61±1.02 years, their average height is 177.68±7.04 cm, their average body weight is 73.89±13.20 kg, and the average body mass index is 23.29±3.57 kg/ cm². The vertical core training experimental group handball players participating in the study performed core training in the vertical plane in addition to the normal training, while the horizontal core training experimental group handball players performed core training in the horizontal plane in addition to the normal training for 8 weeks. The control group, on the other hand, do not participate in any extra training and continued their normal handball training. Experimental and control group handball players are given speed tests (5,10,20,30 meters), agility tests (505-T Test, Hexagon, Illinois), core strength endurance (core stability performance test) in order to determine their levels before and after this 8-week training. tests are applied. In the study, it is observed that vertical core training positively affected agility tests (505, Illinois, Hexagon and T test), while horizontal core training improved core strength, and both horizontal and vertical training improved 20 meters speed. As a result, it is concluded that core training in the horizontal plane affected core strength, while core training in the vertical plane affected speed and agility more than horizontal core training. In addition, in the tests involving running mechanics, it is concluded that vertical core training has a more significant effect than horizontal core training.